The Relation between Anger Management Style and Organ System-Related Somatic Symptoms in Patients with Depressive Disorders and Somatoform Disorders - Koh, Kyung Bong; Park, Joong Kyu (Yonsei medical journal, 2008)
The objective of this study was to examine the relation between anger management style and organ system- related somatic symptoms in depressive disorder and somatoform disorder patients. The subjects included 73 patients with depressive disorders and 47 with somatoform disorders. Anger management styles were assessed by the Anger Expression Scale, while the severity of organ system-related somatic symptoms was evaluated using the Somatic Stress Response Scale (SSRS). The severity of depression and hostility was assessed by the Symptom Checklist-90-Revised (SCL-90-R) depression and hostility subscales. The results of multiple regression analyses showed that, in depressive disorder patients, the level of anger expression was significantly associated with the severity of somatic symptoms related to neuromuscular, cardiorespiratory and gastrointestinal systems. However, in these patients, the level of anger suppression was not significantly associated with the severity of somatic symptoms related to any specific organ systems. In patients with somatoform disorders, there was no significant association between the level of anger suppression or anger expression and the severity of the somatic symptoms related to any specific organ systems. These results suggest that, in depressive disorder patients, anger expression is likely to be predominantly involved in the neuromuscular, cardiorespiratory and gastrointestinal organ systems. However, in each of depressive disorder and somatoform disorder patients, anger suppression is not likely to be associated with any specific organ systems.